2011
DOI: 10.1093/eurjhf/hfr087
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of plasma neutrophil gelatinase‐associated lipocalin in patients with acute heart failure: The NGAL EvaLuation Along with B‐type NaTriuretic Peptide in acutely decompensated heart failure (GALLANT) trial

Abstract: AimsNeutrophil gelatinase-associated lipocalin (NGAL) is a measure of acute kidney injury. Renal dysfunction portends significant risk after discharge from acute heart failure (AHF). Thus, a sensitive marker of renal injury might also help to risk stratify HF patients.Methods and resultsGALLANT [NGAL EvaLuation Along with B-type NaTriuretic Peptide (BNP) in acutely Decompensated Heart Failure] was a multicentre, prospective study to assess the utility of plasma NGAL, alone and in combination with BNP, as an ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
156
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 228 publications
(175 citation statements)
references
References 32 publications
13
156
1
5
Order By: Relevance
“…Furthermore, biomarkers associated with poor renal function (BUN, NGAL, KIM-1, galectin-3) were lower in younger patients [22][23][24][25][26]. This correlates with the finding that younger patients overall had a better renal function at admission and were less often subject to WRF during hospitalization.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, biomarkers associated with poor renal function (BUN, NGAL, KIM-1, galectin-3) were lower in younger patients [22][23][24][25][26]. This correlates with the finding that younger patients overall had a better renal function at admission and were less often subject to WRF during hospitalization.…”
Section: Discussionsupporting
confidence: 53%
“…This is to some extent supported by other studies reporting that plasma NGAL predicts mortality in patients with pre-existing acute cerebral ischemia [18] or chronic heart failure [19,20], although u-NGAL was not evaluated in these studies. The more distinct associations in individuals with pre-existing cardiovascular diseases could also indicate that u-NGAL is an indicator of faster progression of atherosclerosis and chronic heart failure resulting in an increased mortality risk of cardiovascular causes.…”
Section: Discussionmentioning
confidence: 58%
“…Increased concentrations of s-NGAL and u-NGAL are found in patients with chronic heart failure [14,15] and with acute ischemic events [16,17] and increased plasma NGAL concentrations are also associated with a higher risk of mortality in these patient groups [18][19][20] and in the community [21]. However, the prospective association between the tubular kidney damage biomarker u-NGAL and cardiovascular death in the community is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Although not absolutely specifi c for AKI (it is also produced and released by neutrophils) (58) , it is still an early marker of AKI. A discharge value of NGAL > 100 ng/mL, combined with BNP values or even measured alone, has been proven to be a powerful predictor of 30-day adverse outcomes (57) . Finally, a preliminary study has shown that increased plasma levels of asymmetric dimethylarginine (ADMA) are strong and independent predictor of short-and long-term mortality in AHF patients (NYHA Class III/IV) with reduced EF (59) .…”
Section: Laboratory Biomarkersmentioning
confidence: 99%